2014
DOI: 10.1093/molbev/msu256
|View full text |Cite
|
Sign up to set email alerts
|

Standing Genetic Variation Drives Repeatable Experimental Evolution in Outcrossing Populations of Saccharomyces cerevisiae

Abstract: In "evolve-and-resequence" (E&R) experiments, whole-genome sequence data from laboratory-evolved populations can potentially uncover mechanisms of adaptive change. E&R experiments with initially isogenic, asexually reproducing microbes have repeatedly shown that beneficial de novo mutations drive adaptation, and these mutations are not shared among independently evolving replicate populations. Recent E&R experiments with higher eukaryotes that maintain genetic variation via sexual reproduction implicate largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
227
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(245 citation statements)
references
References 43 publications
15
227
2
Order By: Relevance
“…Long time series have recently become available for some E&R experiments (Barrick et al 2009;Burke et al 2010Burke et al , 2014. Standard N e estimators (Krimbas and Tsakas 1971; Nei and Tajima 1981; Waples 1989) assume a small number of generations Ă°tÞ and approximate N e using 2N e t=F: If, however, t=N e is larger, using this approximation can lead to severe bias ( Figure S2).…”
Section: Correction For Two-step Samplingmentioning
confidence: 99%
“…Long time series have recently become available for some E&R experiments (Barrick et al 2009;Burke et al 2010Burke et al , 2014. Standard N e estimators (Krimbas and Tsakas 1971; Nei and Tajima 1981; Waples 1989) assume a small number of generations Ă°tÞ and approximate N e using 2N e t=F: If, however, t=N e is larger, using this approximation can lead to severe bias ( Figure S2).…”
Section: Correction For Two-step Samplingmentioning
confidence: 99%
“…For example, evolution in new habitats may be limited by waiting times for new beneficial mutations (9)(10)(11). Even when adaptation occurs from standing genetic variation, evolution via selection of numerous independent loci of small effect may be time consuming (12)(13)(14)(15)(16). We know, however, that evolution can occur rapidly, particularly under artificial selection or in human-altered landscapes (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…However, several recent findings have called this hypothesis into question. Evidence of interspecific hybridization (4-6), a high level of strain heterozygosity (7,8), and prion transmission (9) have suggested that outbreeding could occur more frequently than previously estimated (9).We calculated the outbreeding rate from the heterozygosity level at polymorphic sites in three genes selected as able to reproduce the topology generated with the genomes of S. cerevisiae (10). Calculation of the outbreeding rate was carried out only on diploid strains for which the sequences of the three genes were available (n = 34; SI Appendix, Table S1), and was based on a modified model, accounting for the possibility of diploid individuals to derive either from intra-ascus mating or from outcrossing (11).…”
mentioning
confidence: 99%
“…However, several recent findings have called this hypothesis into question. Evidence of interspecific hybridization (4-6), a high level of strain heterozygosity (7,8), and prion transmission (9) have suggested that outbreeding could occur more frequently than previously estimated (9).…”
mentioning
confidence: 99%